PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS VIII SMP NEGERI 16 PADANG - Kurniati, Dian; Elniati, Sri (Jurnal Edukasi dan Penelitian Matematika, 2024)
The ability to solve mathematical problems is very important in the learning process. However, tests conducted during observation at SMPN 16 Padang proved that this ability is still at a low level. This study examines the mathematical problem solving ability of students in grade VIII of SMPN 16 Padang using the Problem Based Learning (PBL) approach.  The research design applied was Nonequivalent Posttest Only Control Group Design. The sample was selected by simple random sampling. The t-test analysis on the final test obtained a P-value of 0.024 which indicates that the PBL model is more effective than direct learning in solving mathematical problems.Keywords: Problem Based Learning Model, Mathematical Problem Solving Abilities, Direct Learning